Multiplikasi Murid sebagai Dasar Pendirian Jemaat Baru Menurut 2 Timotius 2:2 - Suwondo, Victorio Emmanuela Sammy; Dewantari, Shinta; Baskoro, Paulus Kunto (Sekolah Tinggi Teologi Kanaan Nusantara, 2025)
This study examines the principle of disciple multiplication as a theological foundation for establishing new congregations based on 2 Timothy 2:2. The main issue addressed is the tendency of contemporary churches to prioritize structural growth over spiritual growth through reproductive discipleship. This research employs a qualitative theological approach using biblical exegesis and missiological analysis. The findings indicate that the layered transmission of faith taught by Paul to Timothy provides a biblical foundation for healthy and sustainable church growth. Disciple multiplication is not merely a ministry strategy but the very essence of the church’s mission, producing new faith communities through continuous processes of spiritual transformation.The important thing in this principle is that the discipleship that is carried out will have an impact on the disciples produced for the establishment of new congregations.AbstrakPenelitian ini mengkaji prinsip multiplikasi murid sebagai dasar teologis bagi pendirian jemaat baru berdasarkan 2 Timotius 2:2. Permasalahan utama yang dikaji adalah kecenderungan gereja masa kini yang lebih menekankan pertumbuhan struktural dibandingkan pertumbuhan spiritual melalui pemuridan yang reproduktif. Penelitian ini menggunakan pendekatan kualitatif teologis dengan metode eksegesis biblika dan analisis teologi misi. Hasil kajian menunjukkan bahwa prinsip pewarisan iman secara berlapis yang diajarkan Paulus kepada Timotius merupakan fondasi alkitabiah bagi gereja yang sehat dan berkelanjutan. Multiplikasi murid bukan sekadar strategi pelayanan, melainkan hakikat misi gereja itu sendiri, yang melahirkan komunitas iman baru melalui proses transformasi rohani yang terus-menerus. Hal penting dalam prinsip ini adalah pemuridan yang dilaksanakan akan membawa dampak murid yang dihasilkan bagi pendirian jemaat baru.